Test of the adiabatic nucleation model in SeTe and GeSnSe glasses - Brasil, V. B.; Meyer, E. (Elsevier B.V., 2004)
Se1-yTey and Ge1-ySnySe2.5 glasses, with compositions Y less than or equal to 0.5 and Y less than or equal to 0.6 respectively, are investigated. These glasses show a glass transition temperature (T-g) above the stability limit, indicated by the Adiabatic Nucleation Model (ANM). This effect has to be so because, other-wise, when cooled, these undercooled liquids would crystallize by generalized nucleation near the stability limit and no T-g could be observed. This shows that Se1-yTey glasses for Y < 0.5 are structurally stable. Limiting cases are pure Te and Se50Te50, which have T'(g)'s on the stability limit. Pure amorphous Te has to be obtained by fast quenching techniques, where the effective (fast quenching) T-g(*) is higher and Se50Te50 tends to crystallize easily. (C) 2004 Elsevier B.V. All rights reserved.